2020
DOI: 10.1186/s12875-020-01254-2
|View full text |Cite
|
Sign up to set email alerts
|

Can patients make heads or tails of enhanced primary health care (EnPHC)? Experience through their own journey

Abstract: Background: Implementation of the new Enhanced Primary Health Care (EnPHC) intervention aims to improve service quality and experience at primary healthcare clinics; especially to newly diagnosed patients. This was achieved by restructuring and improving existing services to better manage non-communicable diseases amongst patients. Objectives of this study are to explore patients' experiences of the EnPHC intervention, to document their feedback and to determine effects of EnPHC intervention on patients. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Twelve papers developed or provided integrated eye care guidelines, protocols, pathways, manuals and training modules for non-eye care specific workers. Intervention strategies included Integrated Management of Neonatal and Childhood Illness protocol and procedures,18 hypertension and diabetes guidelines and care pathways for primary care workers,28 29 37–39 screening protocols for community and hospital health workers to detect vision impairment, cataracts or retinopathy of prematurity,25 30 40 guidelines and training manuals on the management or referral of eye conditions for primary health staff21 22 27 34 and clinical protocols provided in the primary care nursing education curriculum 24…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twelve papers developed or provided integrated eye care guidelines, protocols, pathways, manuals and training modules for non-eye care specific workers. Intervention strategies included Integrated Management of Neonatal and Childhood Illness protocol and procedures,18 hypertension and diabetes guidelines and care pathways for primary care workers,28 29 37–39 screening protocols for community and hospital health workers to detect vision impairment, cataracts or retinopathy of prematurity,25 30 40 guidelines and training manuals on the management or referral of eye conditions for primary health staff21 22 27 34 and clinical protocols provided in the primary care nursing education curriculum 24…”
Section: Resultsmentioning
confidence: 99%
“…Eleven papers described strategies for sharing infrastructure and structural integration with other services including co-locating ophthalmic services with NCD or infectious disease services,36 38–41 integrating eye care indicators within health management information systems,20 project teams sharing space with subregional health offices,19 health supervisors incorporating eye care supervision with other health areas,26 creating a dedicated retinopathy of prematurity screening space and providing more blenders and oxygen saturation monitors in neonatal units,25 counselling services with diabetes care28 and incorporating NCD care in primary health services 29. However, few studies reported any factors impacting integration success.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The EnPHC initiatives consisted of redesigning work processes in the clinic, community intervention through community enrolment and profiling, and improving the referral system between the clinic and hospital. 6 One of the intervention components of the EnPHC is the provision of health education to attending patients. One of the aims of EnPHC is to ensure improvements in patient care experience toward a patient-centered approach using active, population-level strategies for health and wellness.…”
Section: Introductionmentioning
confidence: 99%